Complex Compound Inheritance of Lethal Lung Developmental Disorders Due to Disruption of the TBX-FGF Pathway. - Karolak, Justyna A; Vincent, Marie; Deutsch, Gail; Gambin, Tomasz; Cogné, Benjamin; Pichon, Olivier; Vetrini, Francesco; Mefford, Heather C; Dines, Jennifer N; Golden-Grant, Katie; Dipple, Katrina; Freed, Amanda S; et al. (Am J Hum Genet, 2019)
Primary defects in lung branching morphogenesis, resulting in neonatal lethal pulmonary hypoplasias, are incompletely understood. To elucidate the pathogenetics of human lung development, we studied a unique collection of samples obtained from deceased individuals with clinically and histopathologically diagnosed interstitial neonatal lung disorders: acinar dysplasia (n = 14), congenital alveolar dysplasia (n = 2), and other lethal lung hypoplasias (n = 10). We identified rare heterozygous copy-number variant deletions or single-nucleotide variants (SNVs) involving TBX4 (n = 8 and n = 2, respectively) or FGF10 (n = 2 and n = 2, respectively) in 16/26 (61%) individuals. In addition to TBX4, the overlapping ∼2 Mb recurrent and nonrecurrent deletions at 17q23.1q23.2 identified in seven individuals with lung hypoplasia also remove a lung-specific enhancer region. Individuals with coding variants involving either TBX4 or FGF10 also harbored at least one non-coding SNV in the predicted lung-specific enhancer region, which was absent in 13 control individuals with the overlapping deletions but without any structural lung anomalies. The occurrence of rare coding variants involving TBX4 or FGF10 with the putative hypomorphic non-coding SNVs implies a complex compound inheritance of these pulmonary hypoplasias. Moreover, they support the importance of TBX4-FGF10-FGFR2 epithelial-mesenchymal signaling in human lung organogenesis and help to explain the histopathological continuum observed in these rare lethal developmental disorders of the lung.
Keywords: DNA Copy Number Variations; Female; Fibroblast Growth Factor 10; Gene Expression Regulation; Gestational Age; Humans; Infant, Newborn; Infant, Newborn, Diseases; Lung; Lung Diseases; Male; Maternal Inheritance; Organogenesis; Paternal Inheritance; Pedigree; Polymorphism, Single Nucleotide; Receptor, Fibroblast Growth Factor, Type 2; Signal Transduction; T-Box Domain Proteins

Microcephaly, epilepsy, and neonatal diabetes due to compound heterozygous mutations in IER3IP1: insights into the natural history of a rare disorder. - Shalev, Stavit A; Tenenbaum-Rakover, Yardena; Horovitz, Yoseph; Paz, Veronica P; Ye, Honggang; Carmody, David; Highland, Heather M; Boerwinkle, Eric; Hanis, Craig L; Muzny, Donna M; Gibbs, Richard A; Bell, Graeme I; et al. (Pediatr Diabetes, 2014)
Neonatal diabetes mellitus is known to have over 20 different monogenic causes. A syndrome of permanent neonatal diabetes along with primary microcephaly with simplified gyral pattern associated with severe infantile epileptic encephalopathy was recently described in two independent reports in which disease-causing homozygous mutations were identified in the immediate early response-3 interacting protein-1 (IER3IP1) gene. We report here an affected male born to a non-consanguineous couple who was noted to have insulin-requiring permanent neonatal diabetes, microcephaly, and generalized seizures. He was also found to have cortical blindness, severe developmental delay and numerous dysmorphic features. He experienced a slow improvement but not abrogation of seizure frequency and severity on numerous anti-epileptic agents. His clinical course was further complicated by recurrent respiratory tract infections and he died at 8 years of age. Whole exome sequencing was performed on DNA from the proband and parents. He was found to be a compound heterozygote with two different mutations in IER3IP1: p.Val21Gly (V21G) and a novel frameshift mutation p.Phe27fsSer*25. IER3IP1 is a highly conserved protein with marked expression in the cerebral cortex and in beta cells. This is the first reported case of compound heterozygous mutations within IER3IP1 resulting in neonatal diabetes. The triad of microcephaly, generalized seizures, and permanent neonatal diabetes should prompt screening for mutations in IER3IP1. As mutations in genes such as NEUROD1 and PTF1A could cause a similar phenotype, next-generation sequencing approaches-such as exome sequencing reported here-may be an efficient means of uncovering a diagnosis in future cases.
Keywords: Amino Acid Substitution; Blindness, Cortical; Carrier Proteins; Developmental Disabilities; Diabetes Mellitus; Epilepsy, Generalized; Fatal Outcome; Frameshift Mutation; Heterozygote; Humans; Infant, Newborn; Infant, Newborn, Diseases; Male; Membrane Proteins; Microcephaly; Neurologic Manifestations; Point Mutation; Severity of Illness Index

Neonatal diabetes, gallbladder agenesis, duodenal atresia, and intestinal malrotation caused by a novel homozygous mutation in RFX6. - Concepcion, Jennifer P; Reh, Christina S; Daniels, Mark; Liu, Xiaoming; Paz, Veronica P; Ye, Honggang; Highland, Heather M; Hanis, Craig L; Greeley, Siri Atma W (Pediatr Diabetes, 2014)
Recently, bi-allelic mutations in the transcription factor RFX6 were described as the cause of a rare condition characterized by neonatal diabetes with pancreatic and biliary hypoplasia and duodenal/jejunal atresia. A male infant developed severe hyperglycemia (446 mg/dL) within 24 h of birth. Acute abdominal concerns by day five necessitated exploratory surgery that revealed duodenal atresia, gallbladder agenesis, annular pancreas and intestinal malrotation. He also exhibited chronic diarrhea and feeding intolerance, cholestatic jaundice, and subsequent liver failure. He died of sepsis at four months old while awaiting liver transplantation. The phenotype of neonatal diabetes with intestinal atresia and biliary agenesis clearly pointed to RFX6 as the causative gene; indeed, whole exome sequencing revealed a novel homozygous RFX6 mutation c.779A>C; p.Lys260Thr (K260T). This missense mutation also changes the consensus 5' splice donor site before intron 7 and is thus predicted to cause disruption in splicing. Both parents, who were not known to be related, were heterozygous carriers. Targeted genetic testing based on consideration of phenotypic features may reveal a cause among the many genes now associated with heterogeneous forms of monogenic neonatal diabetes. Our study demonstrates the feasibility of using modern sequencing technology to identify one such rare cause. Continued research is needed to determine the possible cost-effectiveness of this approach, especially when clear phenotypic clues are absent. Further study of patients with RFX6 mutations should clarify its role in pancreatic, intestinal and enteroendocrine cellular development and explain features such as the diarrhea exhibited in our case.
Keywords: Abnormalities, Multiple; Congenital Abnormalities; Diabetes Mellitus, Type 1; Digestive System Abnormalities; DNA-Binding Proteins; Duodenal Obstruction; Fatal Outcome; Gallbladder; Humans; Infant; Infant, Newborn; Infant, Newborn, Diseases; Intestinal Atresia; Intestinal Volvulus; Male; Pancreas; Pancreatic Diseases; Regulatory Factor X Transcription Factors; Transcription Factors